The Effects of Medicinal Plants on Cancer Cell Lines and Efficacy of Experimental Animal Model - Mehmet İbrahim Tuğlu; Işıl Aydemir; Pınar Kılıçarslan Sönmez; Tahir Buran; Mesut Mete (International Journal of Secondary Metabolite)
The use of medicinal plants as an alternative treatment is a historical process and has been known for a long time so that classical treatment can be more effective in wound and cancer treatment. The purpose of this study was to investigate the effects of plant extracts used for therapeutic purposes in cancer cell lines in vitro wound model and in vivo experimental animal model in order to obtain this information. The plants, olive oil (Oleocanthal), mistletoe (Viscum album), Common Centaury (Centaurium erythraea), Momordica charantia, Inula viscosa, Citrus aurantium, Thyme oil (Thymus vulgaris) and algae (Jania longifurca), were used. MCF-7, MB-MDA-231, 67NR and 4T1 for breast, NB2a for neuron, L929 for fibroblast and normal somatic mesenchymal stem cell for comparison were selected for in vitro wound models. As an in vivo breast cancer model, female Balb/c mice were injected with 4T1 cells and skin wound healing in rats was investigated. The effects of medicinal plants were evaluated using MTT assay for viability and proliferation, immunocytochemistry staining NOS for oxidative stress and TGFbeta1 for wound healing. It was found that plant extracts reduced antioxidative damage and inhibited apoptosis. It was observed that oxidative stress and apoptosis were increased in cancer cells, but less effective in invasive cell lines. In vivo experiments showed that wound healing was accelerated and that these rates were achieved with antioxidative and antiapoptotic effects. It has been concluded that medicinal plants are beneficial for treatment of difficult diseases in which patient quality of life is very effective and they should be used as scientific-based medical applications.